Carvone Enantiomers Differentially Modulate IgE-Mediated Airway Inflammation in Mice - Ribeiro-Filho, Jaime (Int J Mol Sci, 2020)
Carvone is a monoterpene found in nature in the form of enantiomers (S- and R-). While previous research has demonstrated the anti-inflammatory and anti-allergic effects of carvone, the influence of carvone enantiomeric composition on its anti-allergic activity remains to be investigated. This study aimed to evaluate the anti-allergic activity of carvone enantiomers in a murine model of airway allergic inflammation induced by sensitization and challenge with ovalbumin (OVA). The oral treatment with R-carvone or S-carvone 1 h before each challenge inhibited the number of leukocytes and eosinophils in the bronchoalveolar lavage (BAL). R-carvone inhibited leukocyte infiltration and mucus production in the lung, which was correlated with decreased production of OVA-specific IgE in the serum and increased concentrations of IL-10 in the BAL. On the other hand, the administration of S-carvone had little inhibitory effect on inflammatory infiltration and mucus production in the lung, which might be associated with increased production of IFN-γ in the BAL. When administered 1 h before each sensitization, both enantiomers inhibited eosinophil recruitment to the BAL but failed in decreasing the titers of IgE in the serum of allergic mice. Our data indicate that carvone enantiomers differentially modulated IgE-mediated airway inflammation in mice. In conclusion, unlike S-carvone, R-carvone has the potential to be used in anti-allergic drug development.